How diet can impact gut microbiota to promote or endanger health. Issue 6 (November 2017) - Chassaing, Benoit; Vijay-Kumar, Matam; Gewirtz, Andrew T.
Abstract : Purpose of review: Disturbances of the intestinal microbiota have been increasingly implicated in driving various diseases associated with a broad range of chronic inflammatory state. Such diseases have increased in incidence since the mid-20th century, and have roughly correlated with societal changes in food production during this period. Recent findings: Considering how changes in diet may have impacted gut microbiota and exploring whether targeted modulations of diet might be a means of optimizing microbiota composition to promote health. Summary: Recent literature demonstrates that modulation of diet has potential to both beneficially and detrimentally impact microbiota composition and how it interacts with its host. Herein, we discuss recent studies by ourselves and others that demonstrate the potential for changes in diet to have profound impacts on the gut microbiota in ways that can have beneficial or detrimental effects on host health.